COLLABORATIVE GOVERNANCE DALAM MEWUJUDKAN LAYANAN “BUY THE SERVICE” PADA PROGRAM TRANS JATIM - Setiyowati, Mita Dwi; Widiyarta, Agus (Universitas Djuanda, 2025)
Public transportation is an alternative to overcoming traffic problems, ranging from reducing congestion, accidents, pollution, and gas emissions. Trans Jatim is a Dinas Perhubungan Provinsi Jawa Timur program with a buy the service system in the Gerbangkertosusila region. This research aims to describe the pattern of collaboration in realizing the service in the Trans Jatim program, to increase the load factor of Trans Jatim Corridor III. The research method used is descriptive qualitative with observation, interviews, and documentation, which is analyzed using Creswell's data analysis technique. Interview activities were conducted with three informants from the East Java Provincial Transportation Office, three informants from PT Yukida Multi Sinergy, and seven informants from Trans Jatim Corridor III service users. The research results show that the collaborative governance process has been implemented to realize the service in the Trans Jatim program by increasing the load factor of Trans Jatim Corridor III. The collaborative governance process has three stages: dynamics, action, impact, and adaptation. In the dynamics of collaboration, there is an operational evaluation forum for Trans Jatim, which presents the government and operators with the results of the policy decision to transfer six bus units from the third corridor to the first corridor. Collaborative action on the policy was implemented since January 1, 2025, with adjustments to bus units and operators assigned to corridors I and III. The impact of the action realizes Trans Jatim services that are right on target, with no bus units operating empty, and the load factor of corridor III is more than 70% which means it has met the target. However, the policy led to public complaints about bus waiting times becoming increasingly long, so adaptation is needed from service stakeholders to evaluate the new policy.